(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
Of the most recent crop of new legislation, perhaps the vegetable most damaged by these jumpers is Law No. 12.016, of August 7, 2009, which regulates the individual and collective writ of mandamus and makes other provisions. Not content with ignoring the historical roots of the writ of mandamus, these jumpers have approached the institute without the indispensable knowledge of experience and under the auspices of a rather clumsy dogma. Of all the improprieties, my attention is drawn to the hermeneutic that has been built around §§ 2 and 5 of Article 7 of the law. The “prohibition” contained in these texts can be sustained on an abstract-textual level, but it doesn’t stand up to a more accurate analysis when looking at the phenomenon from an empirical-normative level. Practice has revealed a real chasm between the general, abstract text and the norm that lives from it. If the legislative text seems to prohibit, in day-to-day legal practice the legal norm that is extracted from it is not so prohibitive. In other words, within the overall normative communication, the laws “preventing” injunctions constitute a weak code.